2019
DOI: 10.1101/850644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary Stalling and a Limit on the Power of Natural Selection to Improve a Cellular Module

Abstract: 10Biological organisms are modular. Theory predicts that natural selection would steadily improve 11 modules towards their performance optima up to the margin of effective neutrality. This classical 12 theory may break down for populations evolving in the clonal interference regime because 13 natural selection may focus on some modules while adaptation of others stalls. Such evolutionary 14 stalling has not been observed and it is unclear whether it limits the power of natural selection to 15 optimize module p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 83 publications
2
11
0
Order By: Relevance
“…These results leverage the findings of Schiffels et al (2011), and later work by Gomez et al (2020) and Venkataram et al (2019), to illustrate that asexual adaptation is not just slower than adaptation with recombination, but differs in other significant aspects. Other models have predicted differences in the nature of adaptation in asexual versus sexual organisms, such as difference in epistasis among fixed mutations (Livnat et al 2008) and, as discussed above, asexuality is linked with extreme generalism in some insects (Gibson 2019).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results leverage the findings of Schiffels et al (2011), and later work by Gomez et al (2020) and Venkataram et al (2019), to illustrate that asexual adaptation is not just slower than adaptation with recombination, but differs in other significant aspects. Other models have predicted differences in the nature of adaptation in asexual versus sexual organisms, such as difference in epistasis among fixed mutations (Livnat et al 2008) and, as discussed above, asexuality is linked with extreme generalism in some insects (Gibson 2019).…”
Section: Discussionsupporting
confidence: 79%
“…Recent theory focusing on asexual evolution has predicted that adaptation among sites with small selection coefficients can be effectively stalled by interference from rapidly evolving sites with larger effects (Schiffels et al 2011). Extending this model to multiple traits, Gomez et al (2019) showed that clonal interference can produce a false signature of trade-offs where none exist, and Gomez et al (2020) showed that a trait with more frequent or larger beneficial mutations can effectively stall adaptation in a trait with lower evolvability, an effect that Venkataram et al (2019) recently demonstrated experimentally. Here, specialization is seen to evolve when a rare environment becomes unprofitable in comparison to the more common environment, solely because of slow relative improvement in how organisms can exploit the rare environment.…”
Section: Introductionmentioning
confidence: 90%
“…For instance, it is possible that early beneficial mutations become deleterious due to further mutations (Zee, et al 2014;Quandt, et al 2015). Furthermore, natural selection may greedily favor mutationally accessible but suboptimal trajectories (Rodrigues and Shakhnovich 2019; Venkataram, et al 2019) that then open new, idiosyncratic paths for further refinement.…”
Section: Discussionmentioning
confidence: 99%
“…All analyses and plots reported in this manuscript have been performed using the R computing environment. The script, modified reference genomes, and raw data (except for raw sequencing data) used for analysis can be found on GitHub at https://github.com/sandeepvenkataram/EvoStalling (83). Raw sequencing data for this project have been deposited into the National Center for Biotechnology Information (NCBI) Sequence Read Archive (SRA) under project PRJNA560969 (84).…”
Section: Methodsmentioning
confidence: 99%